PENGARUH DEBT TO EQUITY RATIO (DER) DAN RETURN ON ASSET (ROA) TEHADAP RETURN SAHAM PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI - Purnomo, Adi Dwi (Universitas La Tansa Mashiro, 2023)
This study aims to determine the effect of Debt to Equity Ratio and Return On Assets on Stock Returns of LQ 45 companies listed on the Indonesia Stock Exchange (IDX). The research method used in this study is a quantitative research method using secondary data types. The sample used was 33 companies for the 2019-2021 period. The amount of data used is 99 data selected by using purposive sampling. The data analysis used was multiple linear regression analysis and processed using SPSS Version 25. The partial results of the t test test Debt to Equity Ratio has no effect on Stock Return. Return On Assets partially affect Stock Returns. The results of the F test simultaneously Debt to Equity Ratio and Return On Assets simultaneously affect Stock Returns.